PHYSICAL PROPERTIES AND MICROSTRUCTURE OF PARTICLE BOARDS BASED ON PALM OIL PALM EMPTY FRUITS AND BAMBOO POWDER WITH A MIXED ADHESIVE OF GAMBIR AND UREA FORMALDEHYDE - Nanda Putri Afrilda; Ety Jumiati; Abdul Halim Daulay (Universitas Islam Negeri Sumatera Utara Medan, 2021)
This test was carried out to reduce waste in coconut empty fruit bunches and to determine the characteristics and microstructure of the particle board surface. The samples used consisted of bamboo powder and oil palm empty fruit bunches with gambier adhesive and urea formaldehyde with variations including: 10%:75%:15%:11%; 20%:65%:15%:11%, 30%:55%:15%:11%, 40%:45%:10%:11%. The particleboard was printed and pressurized using a hot press of 16kg/cm2 for 15 minutes at a temperature of 120 oC, with a drying time of 14 days. The test parameters include: density, moisture content, thickness expansion, and microstructural analysis using SEM (Scanning Electron Microscopy) which refers to SNI 03-2105-2006. The characterization of particleboard produced in the density test is 0.66-0.74 g/cm3, the water content value is 2.4-6.9%, the thickness expansion value is 7.2-12%. Based on the percentage value of the density of the resulting particleboard is a medium density particleboard.